The Entwining Arachnid – Mygale lasiodora - Kalathia, Ghanshyam R. (Homœopathic Links, 2013)
Arachnida is a group of spiders, scorpions and mites. In this article we discuss the spiders and its only two suborders, Mygalomorphae and Araneomorphae with the help of one case.
Keywords: Arachnida; Spiders; Mygalomorphae; Araneomorphae; Mygale lasiodora; Sensation method